Complications of the Endotracheal Tubes for Adult Patients in the ICU - Shamsi , Afzal; Hamidi , Mahsa; Alimardan , Noor; Jasim , Asaad Hayder (Journal of Science in Medicine and Life, 2025)
Background: Patients use intubated endotracheal tubes (ETTs) since they ensure more accurate monitoring of breathing parameters and better ventilation itself. The present work sought to ascertain for adult ICU patients the problems of ETTs. Aims: Assessment the Complications of the Endotracheal Tubes for Adult Patients in the ICU. Methods: This cross-sectional study was conducted on 120 patients hospitalized to Tehran University of Medical Sciences hospitals (Shariati and Imam Khomeini Hospitals) who satisfied the inclusion criteria during 2014–2015 were the subjects of this cross-sectional study. We looked at intubation's problems in them. Data were gathered from a researcher-made questionnaire. Descriptive and inferential statistical tests as well as SPSS version 25 program were used in data analysis. Considered noteworthy was a P-value less than 0.05. Results: The average age of participants was 38.12 ± 9.52 years. The male group had the highest percentage of participants, reaching 56.7%. The average heart rate before the operation was 83.64±9.05, while after using ETT and after the operation, the average heart rate was 79.47±6.44 (p≤0.05). The average systolic pressure before the ETT was 125.56±10.19, while after using endotracheal tubes, the mean systolic pressure was 118.83±9.17 (p ≤ 0.05). The infection rate after using ETT was 31.7%, and it’s the most common complication in patients, followed by bleeding, which reached 17.5% of patients after ETT use. On the other hand, the least common complication among patients using ETT was esophageal intubation, which amounted to 1.7%. The most common reasons for intubation were shock, accounting for 47.5%, and acute respiratory failure, accounting for 32.5%. Conclusions: Finally, the results of this study showed that endotracheal intubation causes changes in the hemodynamic status of patients. Also, the most common problems that can happen during intubation are infection, bleeding, pharyngeal injury, aspiration, laryngospasm, laryngotracheal soiling, and esophageal intubation.